The adaptability and challenges of autonomous vehicles to pedestrians in urban China. (September 2020) - Wang, Ke; Li, Gang; Chen, Junlan; Long, Yan; Chen, Tao; Chen, Long; Xia, Qin
Highlights: Three bad behaviors of Chinese pedestrians are summarized through abundant data. The key technical demands of pedestrians for autonomous vehicles are analyzed. Driverless technologies to protect pedestrians are carefully reviewed. The adaptability of driverless technologies to Chinese pedestrians is analyzed. Abstract: China is the world's largest automotive market and is ambitious for autonomous vehicles (AVs) development. As one of the key goals of AVs, pedestrian safety is an important issue in China. Despite the rapid development of driverless technologies in recent years, there is a lack of researches on the adaptability of AVs to pedestrians. To fill the gap, this study would discuss the adaptability of current driverless technologies to China urban pedestrians by reviewing the latest researches. The paper firstly analyzed typical Chinese pedestrian behaviors and summarized the safety demands of pedestrians for AVs through articles and open database data, which are worked as the evaluation criteria. Then, corresponding driverless technologies are carefully reviewed. Finally, the adaptability would be given combining the above analyses. Our review found that autonomous vehicles have trouble in the occluded pedestrian environment and Chinese pedestrians do not accept AVs well. And more explorations should be conducted on standard human-machine interaction, interaction information overload avoidance, occluded pedestrians detection and nation-based receptivity research. The conclusions are very useful for motor corporations and driverless car researchers to place more attention on the complexity of the Chinese pedestrian environment, for transportation experts to protect pedestrian safety in the context of AVs, and for governors to think about making new pedestrians policies to welcome the upcoming driverless cars.